Enhancing Data Privacy through an Advanced Pseudonym System for Data Anonymization (International Journal of Food and Nutritional Sciences, 2022)
In biometric authentication, large amounts of data are stored on a database server and are accessed via wireless networks and cloud computing techniques. To access the data, we need a unique identification number; otherwise, the data will be authorised by a third party. To circumvent this, we've implemented a Pseudonym System that stores the data between the unique identifier and a biometric authentication method based on the palm vein. During the authentication process, data is stored in the database using anonymous methods and the binary format of pseudo-creation, which can provide a higher level of protection using binary vectors and master key vectors with random key generation to protect user privacy. Nowadays, data privacy and data storage are crucial in all organisations. Cloud Computing and other services are used to store the data. This reduces the time required to receive the result. The third party has no access to the data until he has obtained the unique identifier. Various methods of data anonymization and data privacy are employed here to protect the data.